2016
DOI: 10.3390/ijerph13100985
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Airborne Particles Collected from Car Engine Air Filters Using SEM and EDX Techniques

Abstract: Particulate matter accumulated on car engine air-filters (CAFs) was examined in order to investigate the potential use of these devices as efficient samplers for collecting street level air that people are exposed to. The morphology, microstructure, and chemical composition of a variety of particles were studied using scanning electron microscopy (SEM) and energy-dispersive X-ray (EDX). The particulate matter accumulated by the CAFs was studied in two categories; the first was of removed particles by friction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Based on the morphology and the chemical characteristics of these particle conglomerates, it is probable that this group of particles is associated with the crustal material from soil resuspension. Aluminosilicate agglomerates similar to those observed herein have been reported by Heredia and Rodriguez (2016) in a study conducted in Aguascalientes, Mexico [ 64 ].…”
Section: Resultssupporting
confidence: 88%
“…Based on the morphology and the chemical characteristics of these particle conglomerates, it is probable that this group of particles is associated with the crustal material from soil resuspension. Aluminosilicate agglomerates similar to those observed herein have been reported by Heredia and Rodriguez (2016) in a study conducted in Aguascalientes, Mexico [ 64 ].…”
Section: Resultssupporting
confidence: 88%
“…Studies based on the sampling of CAFs to measure air quality have focused on the monitoring of polycyclic aromatic hydrocarbons (PAHs), polychlorinated dibenzo-pdioxins and polychlorinated dibenzofurans (PCDD/Fs) and some heavy metals in PM 10-2.5 . However, the analysis of the coarse and large PM found in the CAFs has only been reported by Heredia-Rivera and Rodriguez (2016). In this previous work, the presence of PM of biological and inorganic origin in the air of the Mexican city of Aguascalientes was also reported.…”
Section: Particles Retained By Cafsmentioning
confidence: 89%
“…The road surface may contain salt used for de-icing roads, plant fragments, pollen, animal hair and mold, and other biological materials carried from nearby locations [7,8]. The author of this paper [9] conducted an analysis of the contaminants retained on the filter. The contaminant particles varied greatly in size, shape, and chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic particles and synthetic fibers were also found. Analysis of dust particles retained on the filter showed that the most abundant elements found in large irregular particles were C, O, Si, Al, Ca, Mg, Na, K, Ti, Fe, and Si [9].…”
Section: Introductionmentioning
confidence: 99%